IMAGING TECHNIQUES FOR THE DETECTION OF LYMPH NODE METASTASIS IN PATIENTS WITH LARYNGEAL ANF HYPOPHARYNGEAL CANCER - I. G. Frolova; E. L. Choinzonov; V. E. Goldberg; S. Yu. Chizhevskaya; V. I. Chernov; A. V. Goldberg; Yu. V. Belevich (Сибирский онкологический журнал, 2018)
The purpose of the study was a systematic literature review of imaging assessment of lymph node metastasis in patients with laryngeal and hypopharyngeal cancer.Material and methods. In order to review the most relevant scientific literature available, we searched Elibrary, Medline databases (from January 2005 to December 2017). Of 735 identified studies, 32 were assessed.Results. The role of ultrasonography, spiral computer tomography,  magnetic resonance tomography, positron emission tomography in  the assessment of regional metastatic spread in patients with  laryngeal and hypopharyngeal cancer was analyzed. All these imaging techniques failed to reliably identify clinically occult  lymph node metastases. However, the choice of treatment options  for laryngeal and hypopharyngeal cancer depends considerably on  the diagnostic accuracy. In this context, the concept of sentinel lymph nodes deserves special attention.Conclusion. Further studies of the sentinel lymph node concept  using various radiopharmaceutical drugs in the detection of  preclinical regional metastasis in patients with laryngeal and hypopharyngeal cancer are required.